The brittle-ductile transition in silicon. I. experiments - Samuels, J; Roberts, S (Royal Society, 1989)
The experiments described in this paper investigate the fundamental processes involved in the brittle-ductile transition (BDT) in silicon, and form the basis of a new theoretical model (see following paper). The fracture (or bending) stresses of four-point bend specimens of silicon containing semicircular surface cracks, introduced by surface indentation, were determined over a range of temperatures and strain rates. A sharp transition, characterized by a rapid increase in fracture stress with temperature, occurs at a temperature (T$_c$) that depends on the strain rate and the doping of the material used; these data are used to derive activation energies, which are found to be equal to those for dislocation glide. At temperatures above the sharp transition region, the specimens deform by macroscopic plastic yielding. Etch pitting experiments show that below T$_c$ no significant dislocation activity occurs; the sharp brittle-ductile transition is associated with a sudden growth of well-defined dislocation arrays from certain points on the precursor flaw, before fracture occurs. These only appear in a dynamic test at T $\geqslant$ T$_c$; at T = T$_c$, they form only when the applied stress intensity factor K is of the same order as that for brittle failure (K$_{Ic}$) at T < T$_c$. These experiments suggest that at T $\thickapprox$ T$_c$, a 'nucleation' event precedes the generation of avalanches of dislocations when K $\thickapprox$ K$_{Ic}$. Static tests show that dislocations can be made to move from crack tips of K value as low as ca. 0.3 K$_{Ic}$. Above the transition region general plasticity occurs, with slip being concentrated particularly around and spreading from the precursor flaw. A 'warm-prestressing' effect is observed, whereby the low-temperature fracture stress is increased by prestressing above T$_c$.